The Role of Responsible Leadership in Forming an Educational Organizational Culture that Supports the Development of Individual Creativity in Indonesia: A Systematic Literature Review - Meryza Coziffya (Jurnal Sinar Edukasi, 2020)
This study examines how responsible leadership shapes an educational culture that nurtures individual creativity in Indonesia. Using a systematic literature review of peer‑reviewed journals (2020–2024), it synthesizes evidence on the links between leadership, organizational culture, and creativity in education. Findings show that responsible leadership—marked by ethical decision‑making, inclusiveness, and a sustainability orientation—creates collaborative, innovative environments. Such leadership cultivates cultures of openness, adaptability, and experimentation, enabling educators and students to engage in creative and critical thinking. The study also underscores creative talent as a core driver of innovation within educational institutions and the broader creative industries. Integrating digital tools further strengthens outcomes by expanding access to resources and platforms that develop creative skills. In Indonesia’s diverse educational landscape, responsible leadership and supportive culture are pivotal for contributing to the creative economy and addressing complex social challenges. This review contributes to scholarship on leadership, culture, and creativity, offering practical guidance for policymakers, educators, and institutions to pursue strategic collaboration and embed innovative practices that enhance learning and advance sustainable economic development.